An integrated process for xylooligosaccharide and bioethanol production from corncob - Pinpanit Boonchuay (2018)
© 2018 Elsevier Ltd An integrated process for xylooligosaccharides (XOs) and bioethanol production from corncob was investigated. XOs were produced by a consecutive process of KOH treatment and hydrolysis by an in-house thermostable endo-xylanase from Streptomyces thermovulgaris. XO yields of 0.15 g/g KOH-treated corncob (22.13 g/L) and 0.52 g/g raw corncob of cellulose-rich corncob (CRC) were obtained. After 96 h of enzymatic hydrolysis, CRC hydrolysate contained 62.16, 51.21, 10.03 and 0.92 g/L of total sugar, glucose, xylose and arabinose, respectively. Bioethanol production by separate hydrolysis and fermentation (SHF) using CRC hydrolysate, and by simultaneous saccharification and fermentation (SSF) using CRC was studied at 40 °C for thermotolerant Candida glabrata. SHF showed an ethanol yield of 0.28 g/g CRC (21.92 g/L) and ethanol productivity of 0.304 g/L/h with 93% theoretical yield. Surprisingly, by SSF, those parameters were 0.27 g/g CRC (31.32 g/L), 0.33 g/L/h and 89%, respectively. This integrated process might be a new cost-effective approach for corncob valorization.